Understanding Mississippi's Current Practices Concerning Autism Screening at 18 & 24 Months. Issue 4 (1st April 2020) - Jackman, Tiffany C.; May, Warren; Crais, Elizabeth
ABSTRACT: Best practice recommendations by the American Academy of Pediatrics support routine screening for developmental delays in early childhood, specifically at 18 and 24 months for Autism Spectrum Disorder (ASD). During this critical developmental period, early identification and intervention are associated with best outcomes for ASD. Pediatricians perform a critical role in the early recognition of ASD, which can co-exist with other disorders further complicating the diagnosis. However, little is known about the current screening practices in Mississippi. This study provides a unique view of Mississippi pediatricians' perspectives of barriers to routine ASD screening. The intent of this phenomenology study was to better understand current practices and potential barriers, for performing ASD screening at the 18 and 24 month well child visits, as perceived by a sample of Mississippi's pediatric providers. Data collected through key informant interviews were coded to identify commonalities and patterns in responses and aided in the identification of current practices and perceived barriers through qualitative analysis. Although there was increasing implementation of ASD screening by health care providers, routine screening was not consistently conducted. The results suggest a need for a screening tool embedded in the electronic health record for easy access and monitoring. Findings replicated prior studies and endorsed the relevance of barriers that exist in screening Mississippi's youngest population. Mississippi children are at risk of delayed ASD diagnosis if modifications cannot be made to support the clinical environment for pediatricians. Abbreviations: AAP: American Academy of Pediatrics; ASD: Autism Spectrum Disorder; EHR: Electronic Health Record; M-CHAT-R/F: Modified Checklist for Autism in Toddlers, Revised with Follow-Up; CAY: Center for Advancement of Youth; ABA: Applied Behavior Analysis